2011
DOI: 10.1111/j.1475-3995.2011.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model for optimizing the performance of a multi-product production line

Abstract: This paper examines the measures of performance and in particular addresses the throughput of an automated production line processing multiple products. The line is composed of a sequence of workstations connected in series with finite buffers in between. We explore the effects of buffer size on attenuating the impact of line blocking and starvation that can cause a reduction in the output. Such effects are analyzed through a nonlinear mathematical programming model and the implications are examined. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is because DES as an OR technique can be utilized to solve problems in any sector of the economy and to support decision‐making in any operations activities involving service or product. For example, a previous study identified 32 application domains where DES was utilized to solve operations and optimization problems (Abdul‐Kader et al., 2011; Akpan and Brooks, 2012; Akeb and Hifi, 2008; Akpan and Brooks, 2014). As COVID‐19 impacted nearly every sector of the global economy, scientists utilized the DES technique to address pandemic‐related issues in many operational areas and service sectors.…”
Section: Results and Analysismentioning
confidence: 99%
“…This is because DES as an OR technique can be utilized to solve problems in any sector of the economy and to support decision‐making in any operations activities involving service or product. For example, a previous study identified 32 application domains where DES was utilized to solve operations and optimization problems (Abdul‐Kader et al., 2011; Akpan and Brooks, 2012; Akeb and Hifi, 2008; Akpan and Brooks, 2014). As COVID‐19 impacted nearly every sector of the global economy, scientists utilized the DES technique to address pandemic‐related issues in many operational areas and service sectors.…”
Section: Results and Analysismentioning
confidence: 99%
“…Aiming at the optimization of unreliable and imperfect production system, Radhoui et al developed an integrated model based on quality control, preventive maintenance and buffer allocation sizing [45]. Walid et al explored the influence of buffer allocation size on decreasing the impact of production line blocking and starvation, tested the performance indicators and solved the throughput problem of an automatic multi-product production line [46]. To optimize the production system with unreliable machines and inter-operational buffers, Matta et al proposed an output function Kriging approximation-based sequential search method with limited capacity approximated by analytical models [47].…”
Section: Buffer Allocation Researchmentioning
confidence: 99%